Perceived self-competence as a consequence of gender, socio- economic status and birth-order (2001)
The focus of this study Was the main and interaction effects of gender, socio-economic status and birth-order on the perceived self-competence of young. Adolescent. One hundred and twenty Junior Secondary School one, two, three, and SS one-students randomly selected from two schools in Ibadan participated in the study. There was no significant interaction effect of gender, socio-economic status and birth-order on overall self-competence, no main effect of birth-order was also found, however, a significant main effect of gender on self-competence was found.